Removal of Focal Fibrous Hyperplasia on Aesthetic area of Lower Teeth - Alberta, Livia; Haffiyah, Osa Amila (Indonesian Dental Association, 2024)
Focal fibrous hyperplasia is a localized tumor of gingiva, most commonly found on the gingiva. This lesions range in size, from a few millimeters to a centimeter or greater. The Lesions may be sessile or pedunculated, in consistency, and may vary in color from pink to red, depending on the degree of vascularization. It is generally considered a reactive lesion, often associated with chronic irritation or trauma to the gingiva. The aim for this treatment was to obtained the aesthetically approved correction of focal fibrous hyperplasia by excision procedure. A 19 -year-old boy come to University of Gadjah Mada dental hospital with chief complaint enlargement of gingiva on lower anterior tooth, affecting his confidence especially when smiling. This lession have been there for 3 years, since high school. The lession size was 13mm x 5mm x 8mm, with a solid consistency well-defined, same colour as the surrounding oral mucosa, and no evidence of pain. Radiograph showed there was no bone involvement. The treatment of this lesion is excision procedure with gingivoplasty under local anesthesia, followed by biopsy. In conclusion, focal fibrous hyperplasia condition can be corrected by excision procedure with local anesthesia, and also by removing the contributing factors to prevent recurrence. Clinical examination and biopsy are needed to confirm diagnosis.